Measuring situational music performance anxiety – the Polish adaptation of the Performance-related Questionnaire for Musicians - Kaleńska-Rodzaj, Julia; Kotyczka, Michał; Nusseck, Manfred; Spahn, Claudia (Frontiers in Psychology, 2025)
IntroductionMusic performance anxiety (MPA) was mainly assessed using questionnaires that focus on a general predisposition to MPA, detached from a performance. Since performances vary greatly, an appropriate questionnaire should be used to investigate situation-specific MPA. The Performance-related Questionnaire for Musicians (PQM) is an instrument designed to measure situational MPA under live performance conditions. In this study, the Polish adaptation of the PQM has been developed and validated.MethodsSoloists, choral singers, and orchestral musicians (N = 258) completed a battery of self-report inventories immediately after their concert performance.ResultsA confirmatory factor analysis (CFA) model with three factors of the dimensions Symptoms of MPA, Functional Coping, and Self-Efficacy across three time conditions before, during and after the performance showed optimal model fit and confirmed the stability of the factor structure in the original PQM. The reliability coefficients of the subscales were satisfactory, ranging from 0.63 to 0.87. Theoretical validity of the PQM subscales was also supported through correlations with the Performance Anxiety Inventory, Flow Short Scale, and General Self-Efficacy Scale.DiscussionThe Polish adaptation of the PQM constitutes a reliable and valid tool for assessing situational MPA in adult musicians.